Microencapsulação de compostos antociânicos extraídos do mirtilo (Vaccinum spp.) por spray dryer: caracterização, estudo da estabilidade e condições gastrointestinais simuladas - Rosa, Jéssica Righi da (2017)
The growing world population's quest for healthy foods with functional characteristics has leveraged a number of studies with this theme and led industry to adapt to the demands of consumers. Within the functional foods group is blueberry, which contains bioactive compounds in significant amounts. The objective of the present study was the microencapsulation of anthocyanic compounds extracted from the blueberry by the spray dryer method, to test the use of maltodextrin DE20 and to hydrate in different concentrations as encapsulating agents and to verify the stability of the anthocyanin compound and the simulated gastrointestinal conditions. The extract of blueberry was obtained in aqueous solution containing 1% of citric acid and submitted to analyzes of total monomeric anthocyanins, total phenolic compounds and antioxidant activity by the ORAC method. For the microencapsulation process the spray dryer method with different inlet temperatures of 120, 140 and 160 ° C and as encapsulating agent maltodextrin DE20 and hi-meize were used in different concentrations totaling four treatments, where P containing 18% maltodextrin DE20 Was considered to be the standard solution, T1 containing 14% maltodextrin DE20 and 4% hi-m 2, T2 11% maltodextrin DE 20 and 7% hyme, and the formulation T3 where it contained 9% maltodextrin DE20 and 9% hi-meize. The microparticles were analyzed for the determination of total monomeric anthocyanins, total phenolic compounds and antioxidant activity by ORAC method, encapsulation efficiency, particle size, moisture content and water activity, dissolution, color analysis, storage stability study and Analysis of resistance of anthocyanin compounds to simulated gastrointestinal conditions. For analysis of the extract were found values of 1.08 mg / g of fruit for total monomeric anthocyanins, 6.88 mg GAE / d of fruit for total phenolic compounds and 46.85 μm Trolox / g of fruit for antioxidant activity by the ORAC method. In general, a good encapsulation efficiency of the desired compounds can be observed, these values being 74.40 to 85.22%, as well as the obtained particle sizes ranging from 12.80 to 20.70μm. The moisture and water activity presented values from 4.87 to 6.39% and 0.16 to 0.27, respectively. The anthocyanic compounds suffered losses over the course of 20 days in all treatments and temperatures tested, however the T3 formulation microcapsule at 140 ° C showed a better retention and protection of the desired compounds along the days of analysis, as well as greater resistance to conditions Gastrointestinal compared to the free extract, showing effective protection and improved delivery of the compounds of interest. Based on the treatments and temperatures tested it can be concluded that the microcapsules were effective in the protection and improved delivery of anthocyanin compounds.